“Both Sides Now”: Reflecting on Schooling Experiences of Individuals with Disabilities in South Korea - Yoon Joo Lee; Hye Jun Park; Young Eun Jeon; Hye Min Suh (SAGE Open)
This study aims to examine the schooling experiences of four individuals with disabilities in South Korea. It seeks to explore the complexities of their experiences in both inclusive education classrooms and special education schools. This study presents their stories by incorporating counternarratives in which the participants are agentic in producing their narratives, assigning new meaning to lived experiences. Their stories were obtained through a series of three in-depth interviews with each participant. The model of phenomenological interviewing was used to explore the meaning of their experiences in the context of their lives. The findings in this study illustrate multi-faceted and multi-layered aspects of inclusion, encompassing both academic and social experiences. It is crucial to look beyond what is being told about inclusion by the numerical increase of inclusive classroom placements and consider how to create a welcoming community for individuals with disabilities beyond the physical placements of inclusive classrooms or special education schools.